Inhibiting HDAC for human hematopoietic stem cell expansion - Broxmeyer, Hal E. (The Journal of Clinical Investigation, 2014)
In this issue of the JCI, Chaurasia and colleagues report an impressive ex vivo expansion of HSCs from human cord blood (CB) using cytokines and altering epigenetic modifications. The application of this protocol provides information that has potential for clinical consideration. The enhanced expansion of CB HSCs is a substantial advance over recent work from the Chaurasia and Hoffman group, in which ex vivo production of human erythroid progenitor cells from CB was promoted by chromatin modification. Moreover, this study takes advantage of information from the rapidly emerging, but not yet fully elucidated, field of epigenetics.